أﺛﺮ اﺳﺘﺨﺪامﺗﻘﻨﯿﺔ اﻟﺒﻠﻮﺗﻮث ﻓﻲ اﻟﮭﺎﺗﻒ اﻟﻨﻘﺎلﻓﻲ ﺗﺤﺼﯿﻞ اﻟﻄﻠﺒﺔ واﺳﺘﺒﻘﺎﺋﮭﻢ ﻟﻠﻤﻌﻠﻮﻣﺎت (Journal of the College of Education for Women, 2019)
The mobile device be used in all fields in society to be the life is more easy. So that it's used in the instructional operation and that need to study the effective of it in the teaching operation. The aims of research are known the effect of using the Bluetooth techniques in the mobile upon students' achievement and their retention of information. The sample consist of (34) students in the first class in Electrical Techniques Department in Technical Institute of Nassiriayah at (2010 – 2011) which divided to two equivalent groups, experimental and control by using the two equivalent groups design. Seven subjects were choices of Electrical Installation subject in second course. The researcher limited the teaching objectives and built the teaching plans of each group and the final achievement test which consist of (28) questions and doing the psychometrics characterizes by using suitable statistical methods. The teaching operation to the all students is beginning, the students in the two groups teaching the subject together at same time by the teacher. After that the teacher send the more explaining information by the Bluetooth techniques in the mobile about the teaching subject to the students in experimental group while don’t send anything to the students in the control group. The research continue seven weeks and after that the final achievement test is applied to the students in two group at same time and re– applied to them after three weeks as retention of information test. And using suitable statistical methods to analysis the finding and doing the psychometrics characterizes to the research instrument. The finding is supremacy the students in the experimental group which using the Bluetooth techniques in mobile in the achievement and retention of information than the student in the control group which don’t used it. The researcher including the affectivity of the Bluetooth techniques in mobile to increased the achievement of students and their retention of information and they suggest some suggestions that suitable with the finding.